Pengaruh Partisipasi Masyarakat, Transparansi Kebijakan Publik dan Pengetahuan Anggota Dewan terhadap Pengawasan Anggaran Pendapatan Belanja Daerah (Studi Empiris di Kabupaten Bener Meriah) - Fajarsyah Putra; Darwanis Darwanis; Mulia Saputra (Program Magister Akuntansi Unsyiah, 2017)
The purpose of this study was to provide empirical evidence about the public participation, transparency of public Policy, and council’s knowledge for the budget on financial oversight. The population in this research were members of the council who work in the DPRK Bener Meriah regency. The study population were 25 legislators of Bener Meriah from all commission. The research data was obtained from questionnaires. The data analysis method used was multiple linear regression analysis, where public participation, transparency of public and council’s knowledge of the budget control as independent variable, while distrik revenue budget oversight as dependent variable. The results of this study indicated that the public participation, transparency of public, and knowledge council of the budget had effect on local budget oversight.KEYWORDS : Participation, Transparency, Knowledge Council of the Budget, Financial Oversight Area.